Electron‐Irradiation Promoted Exchange Reaction as a Tool for Surface Engineering and Chemical Lithography. Issue 10 (18th March 2021) - Terfort, Andreas; Zharnikov, Michael
Abstract: Self‐assembled monolayers (SAMs) can serve as versatile resist/template materials for surface engineering and electron beam lithography (EBL), making possible a new type of lateral patterning: chemical lithography (CL). Whereas CL has been well established for aromatic SAMs, it is hardly possible for aliphatic monolayers, because of extensive irradiation‐induced damage excluding selective modification of specific chemical groups. Turning this drawback into an advantage, the irradiation‐promoted exchange reaction approach is developed, which is described in detail in the present review. The key idea of the approach is tuning the extent of the exchange reaction between a primary aliphatic SAM covering the substrate and a potential molecular substituent, which is capable of building a SAM on the same support, by electron irradiation. The major advantages of the approach are low irradiation doses (≤1 mC cm −2 ) and flexible choice of SAM‐forming molecules, with a broad pool available commercially. Consequently, a large variety of binary SAMs with controlled compositions can be prepared and, in combination with EBL, complex chemical patterns can be fabricated, serving in particular as templates for subsequent area‐selective chemical reactions, surface‐initiated polymerization, attachment of nanoparticles, non‐specific and specific proteins adsorption, and growth of 3D DNA nanostructures. Abstract : The electron‐irradiation promoted exchange reaction approach, enabling flexible preparation of binary self‐assembled monolayers (SAMs) and chemical litho‐graphy with aliphatic SAMs, is presented. Complex chemical patterns can be fabricated, serving, for example, as templates for subsequent area‐selective chemical reactions, surface‐initiated polymerization, attachment of nanoparticles, non‐specific and specific protein adsorption, and growth of 3D DNA nanostructures.